2022
DOI: 10.1101/2022.01.21.477218
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Beyond Prior and Volatility: The Distinct Iterative Updating Account of ASD

Abstract: Individuals with autism spectrum disorder (ASD) have been widely reported to show atypicalities in predictive coding, though there remains a controversy regarding what causes such atypical processing. Suggestions range from overestimation of volatility to rigidity in the reaction to environmental changes. Here, we tested two accounts directly using duration reproduction of volatile and non-volatile interval sequences. Critically, both sequences had the same set of intervals but differed in their stimulus prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 92 publications
(373 reference statements)
0
5
0
Order By: Relevance
“…This may predict that the contextual inference of the bright sun should be weaker and drive the pupillary response less. However, since the original suggestion by Pellicano and Burr (2012), research suggests that autistic perception is not so much characterized by intrinsically weak priors, but by less flexible priors (Lawson et al, 2017;Shi et al, 2022). In our paradigm there was little unpredictability, with images that were always sun-like, or scrambled.…”
Section: Discussionmentioning
confidence: 92%
“…This may predict that the contextual inference of the bright sun should be weaker and drive the pupillary response less. However, since the original suggestion by Pellicano and Burr (2012), research suggests that autistic perception is not so much characterized by intrinsically weak priors, but by less flexible priors (Lawson et al, 2017;Shi et al, 2022). In our paradigm there was little unpredictability, with images that were always sun-like, or scrambled.…”
Section: Discussionmentioning
confidence: 92%
“…The predictability of the interactional behavior in the present study is one possible explanation for the diminished differences observed between autistic and non-autistic participants. With recent studies showing that temporal predictability might be particularly relevant for performance in autism (Shi et al, 2022), the predictability of timing during social exchange may be crucial for understanding issues with reciprocal interactions in autism and should be investigated further.…”
Section: Discussionmentioning
confidence: 99%
“…The authors interpreted blunted discriminative responses as indications that ASD subjects experienced a mild surprise due to overestimated environmental volatility independent of the true predictability of events. However, because of frequent transitions from stable to unstable task periods, the reversal learning task caused anxious participants with ASD to be subjectively uncertain about any choice they made and to view all options as risky (Shi et al, 2022). Therefore, the atypical pattern of PDR exhibited by subjects with ASD in the reversal learning paradigm, though informative, does not answer the question of why people with ASD lack confidence in tasks in which the choice-outcome contingency is stable, albeit probabilistic.…”
Section: Main Textmentioning
confidence: 99%